PENGARUH FLASH SALES DAN GRATIS ONGKIR TERHADAP PERILAKU KONSUMTIF MAHASISWA PRODI MANAJEMEN FEB UNIVERSITAS MUHAMMADIYAH JEMBER - Mubarok, Muhammad Umam; Wulandary, Dian Anisa; Islami, Riska Dwi; Ramadhan, Akhmad Viqri; Fadhiah, Masyitha Sari; Qomariyah, Nurul (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The development of digital technology has brought about a major change in consumer behavior, especially among the younger generation. This study aims to determine the influence of flash sale and free shipping on the consumptive behavior of FEB Management Study Program students of the University of Muhammadiyah Jember. The population in this study is all students of the Management Study Program FEB Muhammadiyah University of Jember. The sample was determined on the basis of a large sample, which was n â‰¥ 30, in this study a sample of 65 respondents. The sampling method uses simple random sampling. The data analysis method uses descriptive analysis, validity test and reliability test as well as multiple linear regression analysis. The results of the study show that flash sales have an effect on students' consumptive behavior. Free shipping affects the consumptive behavior of FEB Management Study Program students of the University of Muhammadiyah Jember.